UPAYA MENGEFEKTIFKAN FUNGSI MANAJEMEN PADA KOPERASI BINA SEJAHTERA KABUPATEN MUARA ENIM - Novita Sari; . Rismayani (JURNAL KOMPETITIF, 2019)
ABSTRACT The purpose of this study was to determine how to make effective management functions at the Bina Sejahtera Cooperative in Muara Enim Regency. The research method used is the method of observation, interviews, documentation, and literature study. The results showed that the implementation of management functions in the management of the organization at the Gunung Megang Sub-district Bina Sejahtera Cooperative still had many flaws here and there, starting from the first planning or design of activities, supervision and services. It is still constrained by the lack of human resources or lack of management professionals. Keywords: Management Function